UNDERSTANDING THE MECHANISMS OF ABERRANT PROTEIN KINASE A REGULATION IN ACRODYSOSTOSIS MUTANTS WITH HORMONAL RESISTANCE - Della Libera, Leonardo (My University, 2025)
The downstream cyclic-adenosine monophosphate (cAMP) receptor, protein kinase A (PKA), is essential in converting extracellular signals into tightly regulated cellular responses. In cAMP-PKA signaling, these responses are associated with vital processes such as growth, development, and gene expression. Regulation of the kinase, specifically activation and inhibition, is controlled by the binding of cAMP to the regulatory subunit of PKA (R). Several mutations in the ubiquitous RIα isoform of R can cause acrodysostosis 1 (ACRO) – a disease characterized by resistance to thyroid stimulating hormone and parathyroid hormone leading to severe congenital malformations. Previous functional and structural studies have associated ACRO with the hypoactivation of PKA, due to loss of sensitivity to cAMP and the impairment of allosteric networks. In this thesis, we first summarise the clinical and molecular phenotypes of ACRO, and what is currently known about related mutants. We then focus on the R366X truncation mutant which exhibits severe PKA hypoactivation and has been previously studied via x-ray crystallography. However, the crystal structure only captures the inhibited and most stable state of the PKA RIα mutant, and shows minimal difference from the wild type structure. Additionally, previous studies have only examined the effects of ACRO mutants on the activation cycle of PKA (i.e. sensitivity to cAMP binding). In this work, we focus on the less understood signal termination cycle. We hypothesized that R366X acts by perturbing states relevant to this PKA deactivation cycle, which are not visible via static structures. To examine this, our approach combined low- and high-resolution studies to assess protein-ligand binging, mutant stability, and identified regions exhibiting aberrant allosteric behaviours. Based on our results, we propose a novel mechanism where R366X impairs key allosteric mechanisms within PKA, not only impeding proper activation but also hastening cAMP signal termination by accelerating the PKA deactivation mechanism. Our studies contribute to the current understanding of PKA dysregulation and provide methodologies applicable for assessing other ACRO mutants. Through our work, we aim to create avenues for future therapeutic design to counter the effects of these inherited ACRO mutations.